From a Pasty in Cornwall to the Cornish Pasty - Laudan, Rachel (Petits Propos Culinaires, 2014)
The article explores the humble beginnings of the Cornish version of hand-held pies in the context of local history and looks at how these local pasties became an emblem for the "authentic" Cornish experience with the arrival of mass tourism in the early part of the 20th century.